Letter: association of circulating bile acid concentrations and non‐alcoholic fatty liver disease - Sun, Li‐Yang; Ye, Gao‐Qi; Yang, Shun‐Chao; Zhao, Fei; Ma, Sheng‐Zhe; Yang, Tian (Alimentary pharmacology & therapeutics, 2022)
LINKED CONTENT This article is linked to Rivera–Andrade et al papers. To view these articles, visit https://doi.org/10.1111/apt.16948 and https://doi.org/10.1111/apt.17059